Front Cover Image. Issue 9 (14th October 2019) - Grue, Jahn Frederik; Storve, Sigurd; Støylen, Asbjørn; Torp, Hans; Haugen, Bjørn Olav; Mølmen, Harald Edvard; Dalen, Håvard
Abstract : The front cover image is based on the Original Article Normal ranges for automatic measurements of tissue Doppler indices of mitral annular motion by echocardiography. Data from the HUNT3 Study by Jahn Frederik Grue et al., https://doi.org/10.1111/echo.14476 .